If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(6) + y = 5 Multiply 2 * 6 12 + y = 5 Solving 12 + y = 5 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + y = 5 + -12 Combine like terms: 12 + -12 = 0 0 + y = 5 + -12 y = 5 + -12 Combine like terms: 5 + -12 = -7 y = -7 Simplifying y = -7
| -15i^2=0 | | -8(m+8)+2m=94 | | B-48=72 | | 36x^2=18x | | y+(2)=-2 | | 2x+16.5=4x+7.5 | | 0=7x^2-24x+15 | | 5/9(x-32)=-10×9/5 | | (4y-5)(7Y+3)= | | Y-11=-1x-4 | | -2(x-18)=-24 | | -6=7x+2x+3 | | 3(4x+2)=2x-8-4x | | -2.33=-1.2x-2.5 | | 0=7x^2-24+15 | | 3x+18=7x-14 | | -8x+2-10=26 | | 12=r/50 | | x^6-9x^4+14x^2=0 | | 3(x-3)=4x-4 | | -2-x+6x=58 | | 2v+36=8(v-2) | | Y-11=1x-4 | | c/-40=0 | | -54=3x-7x-6 | | 8/24=n/18 | | -9=v-2-2 | | f(x)=4x^5-2x^4+30x^3-15x^2+50x-25 | | 3+6x-x=28 | | 2x^8=15 | | Y=ln(x^2-6x-2) | | 4+3x-5x=4 |